Human Simulation as the Lingua Franca for Computational Social Sciences and Humanities: Potential and Pitfalls - Tolk, Andreas (Journal of cognition and culture, 2018)
The social sciences and humanities are fragmented into specialized areas, each with their own parlance and procedures. This hinders information sharing and the growth of a coherent body of knowledge. Modeling and simulation can be the scientific lingua franca, or shared technical language, that can unite, integrate, and relate relevant parts of these diverse disciplines.